Determination of volatile components of Viscum album L. distributed naturally in Egirdir (Isparta) province, Turkey - Kaytanlioglu, E. H. Tigli; Sarikaya, A. G.; Fakir, H. (Al-Farabi Kazakh Natl Univ, 2022)
This study aims to determining the volatile oil components of naturally distributed Viscum album L. belonging to the Santalaceae family. The study was carried out in villages of Egirdir province of Isparta in Turkey. The isolation of volatile components was performed from of the leaves of the mistletoe collected from five different tree species. Qualitative analysis of volatile components were carried out by the Head Void-Solid Phase Micro Extraction (HS-SPME) technique combined with gas chromatography/mass spectrometry (GC-MS). The identification of the constituents was carried out by comparing the retention index (RI) and mass spectral data (MS) to those reported in the published literature. As a result of the Head Void-Solid Phase Micro Extraction (HS-SPME) technique combined with gas chromatography/mass spectrometry (GC-MS). 54 different components were determined and (E)-2-Hexenal, Benzaldehyde and Nonanal were found as the main components. It is known that there are limited number of studies on the determination of essential oil and volatile components of the Viscum genus. According to this study, the use of mistletoe as a raw material source in different industrial areas have importance.
Keywords: Viscum; volatile components; GC -MS; Isparta; Turkey